Comparative design and hydrodynamic analysis of two myliobatiform-inspired drones - Lloyd, Stephanie; Vasconcellos, Rui [UNESP]; Abdelkefi, Abdessattar; AIAA (Amer Inst Aeronautics & Astronautics, 2020)
The development of new underwater drone technologies, including hydrodynamic performance and bioinspired designs has received significant effort in recent years due to several interests in marine fields. Hydrodynamic analysis on two different myliobatiform shapes, a stingray and a manta ray, is performed by analyzing five different airfoils at appropriate Reynolds number. The results are obtained using different three-dimensional hydrodynamic methods. Design properties are estimated to compute the overall weight, buoyancy, lift, and drag forces. The results are used to determine the optimal airfoil for cruising regime and will be used in further analysis and designing of fixed wing aquatic drones with bioinspired shapes.